2013
DOI: 10.1002/cncr.28376
|View full text |Cite
|
Sign up to set email alerts
|

The symptom burden of cancer: Evidence for a core set of cancer‐related and treatment‐related symptoms from the Eastern Cooperative Oncology Group Symptom Outcomes and Practice Patterns study

Abstract: BACKGROUND A set of common cancer-related and treatment-related symptoms has been proposed for quality-of-care assessment and clinical research. Using data from a large, multicenter, prospective study, we assessed effects of disease site and stage on the percentages of patients rating these proposed symptoms as moderate to severe. METHODS The severity of 13 symptoms proposed to represent “core” oncology symptoms was rated by 3106 ambulatory patients with cancer of the breast, prostate, colon/rectum, or lung,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
181
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 246 publications
(198 citation statements)
references
References 20 publications
(46 reference statements)
7
181
0
1
Order By: Relevance
“…1,6,7 Untreated symptoms are likely to lead to poor quality of life and may lead to nonadherence to cancer treatment regimens. Many current measurement strategies focus on the assessment of symptom prevalence rather than on However, we found that although patients with lung and colorectal cancer in the current study reported a high prevalence of common symptoms, including moderate to severe symptoms, rates of unmet need for symptom management were relatively low.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,6,7 Untreated symptoms are likely to lead to poor quality of life and may lead to nonadherence to cancer treatment regimens. Many current measurement strategies focus on the assessment of symptom prevalence rather than on However, we found that although patients with lung and colorectal cancer in the current study reported a high prevalence of common symptoms, including moderate to severe symptoms, rates of unmet need for symptom management were relatively low.…”
Section: Discussionmentioning
confidence: 99%
“…1,[6][7] Recently, expert panels from the National Quality Forum and ASCO emphasized the importance of patient-reported outcomes, specifically around symptom management in routine cancer care. 2 An understanding of the prevalence and presence of symptoms is important to guiding and implementing care systems to manage symptoms in cancer populations.…”
Section: Introductionmentioning
confidence: 99%
“…FDA published guidelines on the use of PROs emphasize the importance of this concept and their direct recommendation is that the assessment of treatment benefit be established from the patient perspective. This has been further supported by recent seminal publications encouraging the mandatory evaluation of symptoms and the identification of a core set of symptoms integral to clinical benefit in other solid tumor patients [17,18]. Recently, the FDA has approved agents based on symptom improvement coupled with more traditional measures of tumor control in a variety of solid tumors [19,20].…”
Section: Measuring Clinical Benefitmentioning
confidence: 95%
“…More recently, the impact of the occurrence of a core set of multiple symptoms in other solid tumor malignancies has been reported, and the need for measurement in trials evaluating new therapies identified [18,[44][45][46][47]. RTOG 0525 and RTOG 0825 were two of the first brain tumor specific studies to use multiple outcomes measures, including traditional measures of survival and imaging improvement, as well as both symptom and HRQOL PRO measures and objective neurocognitive function, defined as the 'Net Clinical Benefit' (Fig.…”
Section: Future Directions: How To Define Clinical Benefitmentioning
confidence: 99%
“…
Dear Editor,Through the publication of this paper, we intend to catalyse discussion among oncology and palliative care health professionals and researchers on the use of kinesiology taping as an adjunct in the management of symptoms related to cancer.Cancer especially in its advanced stages presents significant morbidity that develops due to physical and psychological manifestations of cancer itself, and/or could be iatrogenic combined with poor health and comorbidities [1,2]. It has been estimated that patients with advanced cancer may have up to 12 concomitant symptoms [1]; some of the most prevalent being pain, fatigue, lack of energy, anorexia/weight loss, constipation, dyspnoea, depression, nausea/vomiting, bloating and oedema [3].
…”
mentioning
confidence: 99%